Arthroscopic screw versus suture fixation in tibial eminence fractures: a systematic review and meta-analysis - Fadlurrahman Manaf; Lukas Widhiyanto; Kukuh Dwiputra Hernugrahanto (Knee Surgery & Related Research)
Abstract Background Tibial eminence fractures are common injuries that can cause significant functional limitations and require timely and effective treatment. Arthroscopic screw fixation and suture fixation are the primary methods used for managing displaced fractures. This study aimed to compare the functional and clinical outcomes between the two groups. Methods An associated systematic review was carried out with Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines utilizing the PubMed, Cochrane Central Register of Controlled Trials (CENTRAL), Sage Journals, Science Direct, and Core Journals databases. Any language publication that assessed the results following the fixation of tibial eminence fractures by screw and suture fixation from 2000 to 2024 was included. Clinical, functional outcomes, subsequent surgeries, complications, operation time, and union time were evaluated. All data were assessed using SPSS version 25 and RevMan version 5.4. Results A total of 9 studies involving 412 patients were analyzed out of 3365 papers. There were no significant differences (p > 0.05) between the two methods in the Lysholm score, Tegner Activity Scale, International Knee Documentation Committee (IKDC) score, range of motion, Lachman test, pivot-shift test, KT-1000, and union time. However, screw fixation had a significantly higher rate of subsequent surgeries (planned removal implant excluded) (29.75% versus 11.6%; p < 0.00001), complications (p = 0.0003), and shorter operation times (67 min versus 85 min; p = 0.0003). Conclusions The findings revealed that suture fixation carried a significantly lower risk of subsequent surgery and complications but required a longer operation time. Each technique presents advantages and challenges, making the decision a crucial aspect of patient care.